2011
DOI: 10.1590/s0104-42302011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à pneumonia nosocomial em indivíduos hospitalizados

Abstract: The findings indicate that arterial hypertension, length of hospital stay of five days and lack of dental floss and mouthwash use are factors likely associated with nosocomial pneumonia, suggesting that these factors should be targeted for effective prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
8
0
7
Order By: Relevance
“…Therefore, its relevance is not limited to the mouth, but saliva can be considered essential to the inflammatory healing of oral, esophageal, and gastric processes [6]. When suppressed or diminished, it causes the feeling of dry mouth, difficulties in swallowing and enhance the risk of development of opportunistic infections [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, its relevance is not limited to the mouth, but saliva can be considered essential to the inflammatory healing of oral, esophageal, and gastric processes [6]. When suppressed or diminished, it causes the feeling of dry mouth, difficulties in swallowing and enhance the risk of development of opportunistic infections [12].…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible risk factors to the decrease in the oral hygiene could be the period of hospitalization equal or longer than 5 days, which suggests that the longer the hospitalization period, the more likely the patient is to develop respiratory infections acquired in the hospital environment [12]. A prospective study [10] concluded that children with longer periods of hospitalization showed the presence of pathogen microorganisms in higher levels than the normal flora, representing a risk for the child.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory diseases are responsible for significant morbidity and mortality in population [1][2][3]. The upper respiratory tract are in intimate contact with the oral cavity through the oropharynx.…”
Section: Introductionmentioning
confidence: 99%
“…However, this balance can be upset quickly when the lack of oral hygiene promotes the accumulation of bacterial biofilm and periodontal disease, causing contamination of the oropharynx and spread to other sites, especially When the natural defense mechanisms are disturbed. This situation is common in the elderly, especially when they lose autonomy to the self-care [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation